Nova enciclopédia portuguesa (Clube Internacional do Livro)
Exemplares nÇ 0015171, 0015176, 0015181, 0015182, 0015183 e 0015180 em depósito / caixa 282. - Exemplares nÇ 0015170, 0015175, 0015174, 0015173, 0015179, 0015178, 0015177 em depósito / caixa 283. - Exemplar nÇ 0015172 em depósito / caixa 355